Analisis Pesan Moral pada Lirik Lagu “You Never Know” Blackpink - Rif'ah Kamilah; Askurifa’i (Bandung Conference Series: Communication Management, 2024)
Abstract. Music and songs as a communication message can convey messages in the context of life. Song lyrics can have a variety of messages. It can contain messages about motivation, culture and morals. In this case, music is an effective communication tool for conveying positive moral messages. Blackpink's song is entitled You Never Know which was released in 2020 feels personal for many people, including the Blackpink members themselves. The aim of this research is to find out the meaning of signifiers in song lyrics You Never Know, the meaning of the sign (signified) in the lyrics of the song You Never Know, and to study the meaning of moral messages in song lyrics You Never Know. This research uses qualitative research methods with a semiotic approach Ferdinand de Saussure and using a constructivist paradigm. The data collection techniques used in this research are text analysis, observation, literature study and interviews. Testing the validity of the data in this research uses source triangulation or what is usually called data triangulation. The results of this research found that there is a moral message in the song "You Never Know" which is related to attitudes of moral courage and humility Abstrak. Musik dan lagu sebagai sebuah pesan komunikasi dapat menyampaikan pesan dalam konteks kehidupan. Lirik lagu dapat memiliki beragam pesan. Didalamnya dapat mengandung pesan tentang motivasi, budaya, maupun moral. Di dalam hal ini, musik merupakan salah satu alat komunikasi yang efektif untuk menyampaikan pesan moral yang positif. Lagu Blackpink berjudul You Never Know yang dirilis pada tahun 2020 terasa personal bagi banyak orang, termasuk member Blackpink itu sendiri. Tujuan penelitian ini adalah untuk mengetahui makna penanda (signifier) pada lirik lagu You Never Know, makna petanda (signified) pada lirik lagu You Never Know, dan untuk mengkaji makna pesan moral pada lirik lagu You Never Know. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan semiotika Ferdinand De Saussure serta menggunakan paradigma konstruktivitis. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah analisis teks, observasi, studi pustaka, dan wawancara. Uji keabsahan data dalam penelitian ini menggunakan triangulasi sumber atau biasa disebut triangulasi data. Hasil penelitian ini menemukan bahwa terdapat pesan moral pada lagu “You Never Know” yang berkaitan dengan sikap keberanian moral dan kerendahan hati.